Pemodelan Regresi Multilevel Pada Pengaruh Masalah Yang Dihadapi Siswa Terhadap Hasil Belajar Matematika - Arie Purwanto (Universitas Islam Jember, 2022)
So far, mathematics is still considered a complex subject to understand. Thus, mathematics learning outcomes in this subject are generally relatively low. Therefore, researchers want to conduct an assessment of the problems faced by students in learning mathematics. The purpose of this research is to know whether or not there is an influence of learning variables, the environment in which students learn, the motivation of students in learning, and the independence students on their learning outcomes. The method chosen is a survey with the snowball sampling method on high school students. The analysis is used in multilevel linear regression analysis. This is doto to obtain or explore more information from the modeling analysis carried out. Based on the research, it was found that there were simultaneous significancenificant simultaneous student’s mathematics learning outcomes. On the other perception, it is also seen that the variability of the grade level is very low which is described as the problem faced for each grade level is not much different. Keywords: learning outcome, multilevel regression